Students Mathematical Representation Ability in Solving Numeracy Problem through Problem Based Learning - Karenina Rizka Alifa; Jeri Araiku; Muhammad Yusup; Weni Dwi Pratiwi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
This research is a descriptive study that aims to explain students' mathematical representation abilities in solving AKM numeracy questions after problem based learning is implemented, to explain the implementation of the problem based learning learning process and to explain students' responses to the problem based learning process. This research was conducted at SMP Negeri 45 Palembang. The subjects of this study were class VIII students in the odd semester of the 2021/2022 academic year. Data collection techniques used are tests, interviews, observations and questionnaires. Then the data were analyzed to get conclusions about the students' mathematical representation ability in solving the AKM numeracy questions after problem based learning was implemented, the implementation of the learning process and students' responses to the learning process with problem based learning. From the results obtained, it can be said that the mathematical representation ability of class VIII.2 students in solving AKM numeracy questions through problem based learning is good with all indicators of mathematical representation abilities appearing such as indicators of verbal representation, symbolic representation and visual representation. Keywords: Mathematical Representation Ability, Numeracy, Problem based learning.